Reconstructing Retirement as an Enterprising Endeavor. (October 2020) - Whiting, Rebecca; Pritchard, Katrina
This article explores issues of age and enterprise in later life as manifested in tensions between retiree and entrepreneurial identities. We utilize the concept of a discursive event to examine time-bound online data, specifically media texts and reader comments associated with the online news coverage of an insurance company report. This report introduced the label Weary to describe "working entrepreneurial and active retirees." Our analysis shows how keeping healthy and active are constructed as insufficient markers of a productive and successful older age. These markers are supplanted by a neoliberal discourse that prioritizes enterprise and economic productivity in retirement. However, the Weary subject position has implications within this discourse that constrain the valued contribution of older adults to productive work yet deny access to this group to entrepreneurial endeavors. This highlights the destabilization of retirement and critical tensions in its discursive reconceptualization as a period of entrepreneurial endeavor.